The complete mitochondrial genome of the Indian dammer bee, Tetragonula iridipennis, and the phylogenomics of Meliponini - Karuppaiah, Vadivelu; Gadge, Ankush S.; Shirsat, Dhananjay V.; Soumia, Parakkattu S.; Mainkar, Pawan; Kumar, Satish; Jaiswal, Durgesh K.; Mahajan, Vijay (Frontiers in Ecology and Evolution, 2023)
The Indian stingless bee, Tetragonula iridipennis (Hymenoptera: Apidae) popularly recognized as Indian dammer bee is an economically important and widely distributed non-Apis bee species in India. The taxonomic gaps, systematics, evolutionary puzzles and structural motifs within mitogenomes of this species have rarely been examined and not fully understood. Next-generation sequencing was employed to decipher the complete mitochondrial genome of T. iridipennis (15,045 bp). The results of de novo genome assembly revealed that it encompasses 34 genes: protein-coding genes (13), transfer RNA (tRNAs) genes (19), and ribosomal RNA (rRNA) genes (2). The genome organization including gene content, nucleotide composition, codon usage and gene rearrangement were also investigated for better comprehension, utilization and conservation of this germplasm resource. The average gene length was 400bp; maximum and minimum length were 1530 bp of cox1 and 57 bp of tRNA-S1, respectively. Phylogenetics divulges that T. iridipennis has closest affinity with T. pagdeni and Lepidotrigona species. All the stingless bee species (Meliponini) formed a distinct clade that share a closer relationship with bumble bees (Bombini) than honey bees (Apini). Nucleotide composition of T. iridipennis was biased towards A+T with 75.95% of whole mitogenome. Length and compositional differences between T. iridipennis and other bees were detected and gene order was compared. The mitogenome of T. iridipennis showed the highest gene rearrangement score (78), suggesting this species has a hyperactive evolutionary history. The variations of gene positions and gene rearrangement in mitogenome could also aid in resolving the phylogenetic relations and evolutionary history in Meliponini. Also, this is the first report of complete mitochondrial genome sequence of T. iridipennis.